(untitled) - Am, Alice; Trapiella-Alfonso, Laura; Lescot, Camille; Doan, Bich-Thuy; d’Orlyé, Fanny; Varenne, Anne (Comptes Rendus. Chimie, 2025)
This study presents the journey of a collaborative project for the development of biocompatible nanotheranostic tools, based on peptide self-assembling nanostructures. The peptide sequences were designed to combine smart drug delivery and imaging properties. For this purpose, the selected sequences present: (1) an amphiphilic character for self-assembling properties, efficient hydrophobic drugs encapsulation and efficient biodistribution; (2) a pH-sensitive self-assembly for drug delivery under pH modification in the environment of cancer cells; (3) a receptor-targeting motif within the peptide sequence, overexpressed by certain cancer cells, for specific and controlled delivery of the active ingredient to tumors; (4) accessible functions for further functionalization with a contrast agent for diagnosis. These sequences were first synthesized in a continuous flow to provide a rapid and versatile synthetic process, while lowering reactant consumption, and the synthetic route was optimized through the development of an electrokinetic method coupled to UV–visible detection (CE-UV) and mass spectrometry (CE-MS) that allowed a powerful physicochemical characterization in terms of sequence identification and purity. Few pertinent peptide sequences were then functionalized with a complex of gadolinium to generate Magnetic Resonance Imaging (MRI) properties, and this functionalization step was also optimized and controlled by CE-MS. The formulation procedure was then developed by a deep physicochemical characterization of the peptide nanostructures and the combination of analytical and physical methods to highlight the mechanisms generating the quick reversible self-assembly. Finally, MRI imaging studies on both monomers and nanostructures evidenced a good MRI contrast with properties adapted for a short half-life time.